Islamic Law and Muslim Same-Sex Unions, Junaid Jahangir and Hussein Abdallatif - Mahomed, Nadeem (Journal for Islamic Studies, 2018)
The last decade has witnessed an extensive number of offerings on the subject of same-sex sexuality in the context of Islam. These offerings now include some scholarly responses to the arguments furnished by advocates for integrating LGBTQ people and their rights within a religious framework. This rich output demonstrates the increasing importance that sexual identity and sexual diversity is playing in the public sphere globally; the recognition of same-sex marriage in the first Asian nation, Taiwan, is an example of this. More importantly it demonstrates the initiatives of LGBTQ Muslims, in becoming more vocal and visible in their lives, as well as their activism and their engagement with the Islamic legal tradition. Amongst the many monographs and articles on same-sex eroticism and Islam, there are some which specifically make the case for the permissibility of same-sex marriage in Islam. Jahangir’s and Abdallatif’s work fits into this genre and complements it insofar as it exclusively focuses on aspects of the Islamic legal tradition to put forward a case for the legitimacy of same-sex unions within the ambit of the shariah.